Trend of changes in antibiotic resistance in Helicobacter pylori from 2013 to 2019: a multicentre report from Taiwan. (December 2020) - Liang, Chih-Ming; Tai, Wei-Chen; Hsu, Pin-I; Wu, Deng-Chyang; Kuo, Chao-Hung; Tsay, Feng-Woey; Lee, Chia-Long; Chen, Kuan-Yang; Chuah, Seng-Kee
Background: Antibiotic resistance plays a crucial role in the treatment failure of Helicobacter pylori (H. pylori) infection. This study aimed to determine the trend of changes in the primary, secondary and tertiary antibiotic resistance of H. pylori in Taiwan over the last 7 years. Methods: We retrospectively analysed H. pylori -infected isolates from patients with primary resistance ( n = 1369), secondary resistance ( n = 196) and tertiary resistance ( n = 184) from January 2013 to December 2019. The H. pylori strains were tested for susceptibility to amoxicillin, clarithromycin, levofloxacin, metronidazole and tetracycline using the Epsilometer test method. Results: A progressively higher primary resistance rate was observed for clarithromycin (11.8–20.4%, p = 0.039 in χ 2 test for linear trend), levofloxacin (17.3–38.8%, p < 0.001) and metronidazole (25.6–42.3%, p < 0.001) among naïve patients who received first-line eradication therapy. The dual primary resistance to clarithromycin and metronidazole also progressively increased in a linear trend (2.4–10.4%, p = 0.009). For secondary resistance, an increase was observed for levofloxacin (30.5–64.7%, p = 0.006) and metronidazole (40.5–77.4%, p < 0.001). For tertiary resistance, the observed increase was even more significant for levofloxacin (65.9–100.0%, p = 0.106) and metronidazole (44.4–88.2%, p < 0.001). The resistance to amoxicillin and tetracycline remained very low in Taiwan regardless of primary, secondary and tertiary resistance. Conclusion: Primary, secondary and tertiary antibiotic resistance to clarithromycin, levofloxacin and metronidazole for H. pylori has been increasing in Taiwan since 2013. Treatment should be targeted for eradication success rates of more than 90%. Third-line treatment should be based on antibiotic susceptibility.